Approaches to evaluating landscapes for tourism development planning purposes with application to the marshes (Journal of the College of Basic Education, 2023)
This research aims to identify landscape evaluation methods for the purposes of development planningpolitical; And applying these approaches to the marshlands in southern Iraq. So it was splitThe research is divided into two main parts: the first represents the theoretical basis for the research, which includes typesand elements of these curricula. The second included the application of these approaches to the southern marshesIraq, using the results of the questionnaire conducted by the researcher. The research presented three strategiesTo develop the area as far as the subject matter of the study is concerned are: conservation strategy; strategyprotection; improvement strategy.